Сборка шатунно-поршневой группы двигателей внутреннего сгорания - Святуха, А. А.; Подоляк, О. С. (НТУ "ХПИ", 2008)
В роботі запропонована конструкція напівавтомата, розробленого в Українській інженерно-педагогічній академії, за допомогою якого можливо підвищити якість і продуктивність з’єднань з натягом шатунно-поршневої групи двигунів внутрішнього згоряння.

In this article semiautomatic device is suggested, which was developed in the Ukrainian Engineering-Pedagogical Academy. This device can increase the quality and productivity of assembly with stretching connecting rod-piston group of the internal combustion engine.
Keywords: автомобильный кран; индукционно-тепловая сборка; центрирующая оправка; нагрев